Thermal stability of metallic nanowires and microspheres - Gordon, Eugene B. (Хабаршы. Физика сериясы, 2015)
Quantized vortices in superfluid helium are the perfect one-dimensional template, imposing growing the product of condensation of any impurities suspended in HeII only along the core of the vortex. Nevertheless, we have demonstrated that it is impossible in the case of metal to prepare the chain of single atoms or molecules.